Nutrition and gastrointestinal parasitism in ruminant production - Basabe, Julia (2008)
In order to increase ruminant performance, producers have to deal with two main obstacles: health and nutrition. Resistance to traditional anthelmintic drugs and the increasing "organic production" of food are demanding alternative parasite control methods. When cattle parasites alter food intake and cause a lower use of the absorbed nutrients, they greatly interfere with productivity. "Immunonutrition" is considered a potential and sustainable method of antiparasitical control. Protein, vitamin and mineral availability are important factors to optimize production and the resistance of the host to certain parasites. Secondary substances of some plants can have antiparasitical effects in animals grazing on them. The purpose of this work is to, based on a review of previous research studies, point out some of the existing interactions between nutrition and parasitism in ruminants, and to show how a rational nutritional management can be seen as an efficient antiparasitical control method.